HUBUNGAN ANTARA KECERDASAN EMOSIONAL DENGAN INTENSI BERWIRAUSAHA PADA SISWA SMK NEGERI 44 JAKARTA - Khoerunnisa, K; Zain, Nuryetty (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2014)
This research has purpose to get valid and reliable data about the relationship between emotional quotient and entrepreneurial intention on students 44 State Vocational High School in Jakarta. The research was conducted by survey method with correlation approach. The population in this research were all students at 44 State Vocational High School in Jakarta. Affordable population in this research were the students in XI Department Administrative office, Accounting, and Marketing amount to 192 students. Total of samples used were 123 students research. Sampling technique used in the form of a questionnaire with 30 statements to variable of emotional quotient and 24 statements to variable of entrepreneurial intention. From requirement analysis test conducted, the data is normally distributed by linear regression equation Y = 58,04 + 0,55X. By calculating the correlation coefficient for emotional quotient (X) to entrepreneurial intention (Y) was 0,4276 which is shows that the correlation is strong. Base on calculation of the coefficient determination was obtained 0,1828 or 18,28%. It showed that 18,28% of emotional quotient affect students entrepreneurial intention, while the remaining 81,78% is influenced by other variables that are not described in this model. Key words : Entrepreneurial Intention, Emotional Quotient